An Evaluation of the Menu Representation of Local Cuisines in the Context of Gastronomy Tourism, Social Economy, and Local Development: The Case of Elazığ Restaurants (Third Sector Social Economic Review, 2026)
This study analyzes the extent to which Elazığ's rich culinary heritage contributes to social economy and local development objectives through gastronomy tourism. The research is based on menu analysis of 12 restaurants in Elazığ city center and semi-structured interviews with their operators. Findings reveal a significant representation problem for local dishes despite the rich cultural heritage. The fact that only 14% of the 133 cataloged local dishes are featured on menus indicates a structural gap in transforming this value into a tourism product and a sustainable local economic model. Operators' culinary knowledge relies on informal social networks (master-apprentice, family) rather than formal education, limiting the transfer of this cultural capital. Apart from a few popular dishes (e.g., içli köfte, Harput köftesi), many authentic flavors remain outside commercial circulation. Sourcing difficulties underscore the weak linkages between local producers and restaurants, posing a primary barrier to integration. Consequently, Elazığ's gastronomy tourism potential is high; however, its evolution into an inclusive local development model and a sustainable social economy requires strategic interventions that strengthen local supply chains and prioritize education.
Keywords: Local Dishes; Gastronomy Tourism; Social Economy; Local Development; Elazığ Cuisine; Restaurant Menus